Optimalisasi Peranan Live Music dalam Meningkatkan Loyalitas Pelanggan Seven Sky Yogyakarta - Lahmi Achmad; Zulhaq Khomeini (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2023)
Seven Sky Yogyakarta has provided live music facilities as one of its attractiveness as a tourism destination. Therefore, this research like to know how much the contribution of live music is in influencing customer loyalty so that visitors still come. This is descriptive research with a quantitative methodology. Data collection was carried out by conducting a survey by distributing questionnaires to 350 samples from the population who were visitors of the Seven Sky Yogyakarta. The sampling technique used is the convenience sampling method. Data analysis was performed using multiple regression analysis using the t-test and F-test. The results showed that partially musical ability, stage appearance, facilities, and audience interaction have a significant effect on customer loyalty. Partially, the musician's appearance and musical sound have similar effects, but insignificantly. Simultaneously all these independent variables have a significant effect on customer loyalty.